Male Involvement in Maternal Health Planning Key to Utilization of Skilled Birth Services in Malindi Subcounty, Kenya - Lilian Nyamusi Nyandieka; Mercy Karimi Njeru; Zipporah Ng’ang’a; Elizabeth Echoka; Yeri Kombe (Advances in Public Health)
Background. In Malindi, rural populations face challenges in accessing skilled birth services. Consequently, the majority of women deliver at home and only seek help when they have complications. This paper reports part findings from a study conducted to assess health priority setting process and its implication on availability, access, and use of emergency obstetric care services in Malindi. Methods. The study utilized qualitative methods to collect data from health personnel and maternal health stakeholders including community members. Source and method triangulation was used to strengthen the credibility of study findings. Data was categorized manually into themes around issues relating to utilization of skilled birth services discussed in this paper. Findings. Various barriers to utilization of skilled birth services were cited. However, most were linked to mwenye (the husband) who decides on the place of birth for the wife. Conclusion. Husbands are very influential in regard to decisions on skilled birth service utilization in this community. Their lack of involvement in maternal health planning may contribute as a barrier to utilization of skilled care by pregnant women. There is need to address the mwenye factor in an attempt to mitigate some of the barriers cited for nonutilization of skilled birth services.